Ubiquitin-Proteasome Protocols
DOI: 10.1385/1-59259-895-1:305
|View full text |Cite
|
Sign up to set email alerts
|

Aggresome Formation

Abstract: Bulk protein degradation in the cell is catalyzed by the ubiquitin-proteasome system (UPS). At the heart of the UPS is the proteasome, a large multisubunit tightly-regulated protease. The UPS performs key functions in protein quality control by monitoring and eliminating potentially toxic misfolded or damaged proteins. When the capacity of this protease system is exceeded, misfolded protein substrates aggregate and are assembled through an active and regulated process to form an aggresome. Aggresomes are dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 0 publications
2
55
0
2
Order By: Relevance
“…7B; refs. 18,19,26). Longer image capture (exposure) revealed that essentially all of the VCP-GFP fusion protein had been depleted from the cytoplasm, and no residual VCP-GFP fluorescence remained on ER membranes or on drug-induced vacuoles (data not shown).…”
Section: Geldanamycin Plus Velcade Redistributes Vcp Away From the Ermentioning
confidence: 89%
See 1 more Smart Citation
“…7B; refs. 18,19,26). Longer image capture (exposure) revealed that essentially all of the VCP-GFP fusion protein had been depleted from the cytoplasm, and no residual VCP-GFP fluorescence remained on ER membranes or on drug-induced vacuoles (data not shown).…”
Section: Geldanamycin Plus Velcade Redistributes Vcp Away From the Ermentioning
confidence: 89%
“…These observations prompted us to hypothesize that a buildup of misfolded, nondegradable Hsp90 client proteins might be responsible for the enhanced cytotoxicity of this drug combination (20). Both 17-AAG (5,10) and Velcade (22)(23)(24)(25) show promising clinical activity against various human cancers, and these drugs are currently in multiple advanced combinatory trials with standard first-line anticancer drugs (9,26). Recently, a phase I clinical trial of 17-AAG combined with Velcade was initiated at several cancer research centers.…”
Section: Introductionmentioning
confidence: 99%
“…27 Aggresomes are rich in ubiquitin, 19S and 20S proteasome subunits, and the chaperones Hsp70 and Hsp90. 28 Additionally, aggresome formation triggers redistribution of vimentin intermediate filaments from cytoplasmic networks to a cage-like structure surrounding the aggresome core. 22 Thus, when the capacity of the proteasome is exceeded, as in cases where toxic proteins are overexpressed, 29 a dramatic cellular response involving cytoskeletal reorganization and trafficking events ensures that misfolded/damaged proteins are sequestered along with ubiquitin-proteasome and other quality-control components specifically at the centrosome.…”
Section: The Ubiquitin-proteasome System In Eukaryotesmentioning
confidence: 99%
“…28,36,37 Indeed, isolated examples of centrosomally-degraded substrates involved in a host of biological processes continue to emerge, which we discuss below (Individual examples covered in this review are shown in Fig. 1).…”
Section: The Ubiquitin-proteasome System In Eukaryotesmentioning
confidence: 99%
“…Aggresomes, another class of intracellular protein accumulation, arise due to incomplete proteasomal degradation of misfolded proteins. Aggresome formation is microtubule dependent and occurs due to assemblage of smaller aggregates in the cell to the MTOC area (276). Both of these intracellular sequestration mechanisms retain proteins in the cell although in different locations.…”
Section: Discussionmentioning
confidence: 99%